The church and LGBTQ: Towards the church as an inclusive communion of disciples - Setyawan, Y.B. (Acta Theologica, 2022)
Some churches worldwide, including those in Indonesia, practise ecclesial discrimination against lesbian, gay, bisexual, transgendered, and queer (LGBTQ) individuals, as manifested in the rejection of their existence. In this article, I discuss the LGBTQ issue faced by churches and I argue that it is essential for the church to become an inclusive communion of Jesus’ disciples that embraces all believers, including LGBTQ individuals, who experience salvation thanks to God’s grace. To become such an inclusive community, the church must be open to seriously consider three important points, namely the scientific findings of LGBTQ, especially in the medical and psychological fields; the latest theological views on LGBTQ and new ways of interpreting the biblical text, as well as an ecclesiological reconstruction of the essence of the church as an inclusive communion of disciples.